Transparent Façade Panel Typologies Based on Recyclable Polymer Materials - Giles, Harry; Kim, Kyoung-Hee (Enquiry The ARCC Journal for Architectural Research, 2007)
Buildings are large consumers of energy. In the United States of America; they constitute over 33% of the total annual energy consumption, produce 35% of the total carbon dioxide emissions and attribute 40% of landfill wastes. The building industry is also a large consumer of non-renewable materials and this trend has escalated dramatically over the past century. It is essential that we find ways to save on energy consumption through the use of solar energy, improved thermal insulation, and alternative efficient glazed façade systems. In this paper, we demonstrate how alternative typologies of transparent and translucent load-bearing façade systems based on biocomposite and recyclable materials, are structurally and thermally efficient at the same time they contribute towards reduced pollutant emissions and non-renewable material uses.Composite insulated panel systems are used extensively in the engineering and building industry, owing to their structural and thermal efficiency. However, these systems are generally opaque and offer little flexibility in building applications. As an alternative, we demonstrate how building products comprised of hybrid material typologie scan be made to perform efficiently as load-bearing façade systems that substitute for current glazing systems with adequate thermal and structural performance, which also possess good light transmission characteristics and integral shading capability. The materials are configured to work as composite panel systems made from a combination of biocomposite and recyclable polymer materials. These materials are environmentally sustainable, because they either originate from naturally grown renewable resources or are recyclable. Our research program includes the design and development of prototype panel systems; the evaluation of structural and thermal performance, together with their role in reducing energy consumption and pollution emission through life cycle analysis. The paper describes relevant applications and related current research activities, being carried out by the authors, under an EPA/NSF funded grant project, titled People, Prosperity and Planet, in relation to prototypical composite panel systems. Our current area of investigation relates totypologies that use thermoplastic polymers (as skin material) and biocomposites (as a core material). Our evaluations have demonstrated viable applications and improved performance compared to conventional single and double glazing systems in buildings. The paper also discusses the fundamentals of the research investigations and predicts good energy efficiency, making the product a sustainable alternative when used in building applications. The paper highlights areas of ongoing research and applications for hybrid composite façade systems, which will make the approach a viable option for the building industry, in the future.